2016
DOI: 10.1016/j.nima.2015.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Path to AWAKE: Evolution of the concept

Abstract: This report describes the conceptual steps in reaching the design of the AWAKE experiment currently under construction at CERN. We start with an introduction to plasma wakefield acceleration and the motivation for using proton drivers. We then describe the self-modulation instability -a key to an early realization of the concept. This is then followed by the historical development of the experimental design, where the critical issues that arose and their solutions are described. We conclude with the design of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 73 publications
1
79
0
Order By: Relevance
“…Alignment between proton and laser beams (and thus plasma) is obtained and maintained using beam position monitors and a virtual laser line. The SSM process develops along the plasma with saturation expected before its end [24]. At saturation the microbunches are fully formed and propagate towards the plasma end and diagnostics.…”
mentioning
confidence: 99%
“…Alignment between proton and laser beams (and thus plasma) is obtained and maintained using beam position monitors and a virtual laser line. The SSM process develops along the plasma with saturation expected before its end [24]. At saturation the microbunches are fully formed and propagate towards the plasma end and diagnostics.…”
mentioning
confidence: 99%
“…Extensive recent studies and computer simulations have indicated that a high energy proton bunch is capable of exciting strong electromagnetic wakefields in a plasma which can accelerate a bunch of electrons to the energy frontier of up to a TeV in energy in a single stage of acceleration [8], [9]. If proton beams from existing high energy proton colliders e.g.…”
Section: Proton-driven Plasma Acceleration: Awakementioning
confidence: 99%
“…It will be implemented in the SPS beam extraction cave area originally used for generating neutrinos via a high power target for the Gran Sasso experiment. A pan-European collaboration has been formed for a few years now [9] and commissioning is just beginning. The current AWAKE time line involves initial running in 2016 for 4 weeks equivalent of continuous running with proton-beam commissioning, a Phase 1 of initial data-taking and a Phase 2 of further fabrication and installation of the plasma column and electron injector during calendar years 2017 and 2018, followed by a Long Shutdown for 24 months during calendar years 2019 and 2020, followed by serious systematic wakefield Acceleration studies.…”
Section: Proton-driven Plasma Acceleration: Awakementioning
confidence: 99%
“…A very similar problem arose recently in the context of the Advanced Proton Driven Plasma Wakefield Acceleration Experiment (AWAKE) experiment at CERN. AWAKE is a proton-driven plasma wakefield acceleration experiment, the first of its kind, which uses high-energy proton bunches to drive wakefields in a plasma for electron acceleration [6][7][8]. Central to the device is a 10 m long rubidium vapor cell where the proton bunch interacts with the plasma serving as an energy exchange medium between the protons and the injected electrons.…”
Section: Introductionmentioning
confidence: 99%